2022
DOI: 10.1111/gbi.12535
|View full text |Cite
|
Sign up to set email alerts
|

Active and dormant microorganisms on glacier surfaces

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 149 publications
0
10
0
Order By: Relevance
“…Previous work has also identified that a subset of taxa in Greenlandic seasonal supraglacial snowpacks and meltwater channels are potentially active whereas others are translationally quiescent (Gokul et al, 2019). There is recent evidence that at least half of the cells in glacier surface habitats are translationally active within typical summer conditions, and can rapidly resume activity upon defrosting, well within the likely residence time of meltwater within the weathering crust (Bradley et al, 2023; Stevens et al, 2018). Furthermore, our finding that the exported community from the glacier surface is dominated by Polaromonas concurs with RNA‐based studies of fluvial export from Canadian Arctic watersheds which show Polaromonas as a key constituent of the potentially active exported microbiome (Comte et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has also identified that a subset of taxa in Greenlandic seasonal supraglacial snowpacks and meltwater channels are potentially active whereas others are translationally quiescent (Gokul et al, 2019). There is recent evidence that at least half of the cells in glacier surface habitats are translationally active within typical summer conditions, and can rapidly resume activity upon defrosting, well within the likely residence time of meltwater within the weathering crust (Bradley et al, 2023; Stevens et al, 2018). Furthermore, our finding that the exported community from the glacier surface is dominated by Polaromonas concurs with RNA‐based studies of fluvial export from Canadian Arctic watersheds which show Polaromonas as a key constituent of the potentially active exported microbiome (Comte et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The standing theory for inoculation of the supraglacial environments by bacteria is that they are delivered through aerial deposition (Šantl-Temkiv et al 2018 , Cameron et al 2020 ). Once on the ice sheet, a significant portion of glacier surface microbes are subsequently found to be metabolically inactive (Bradley et al 2022 ). This means certain taxa of microbes observed in this study through culturing might spring from transient cells in the sample they were captured from, rather than settled and thriving colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Supraglacial and subglacial microbial communities have been widely studied and characterized in the last few decades, with many studies showing how biotic and abiotic processes in these systems are linked to global biogeochemical cycles [ 4 , 34 , 35 ]. It is also common knowledge that climate warming affects the interconnectivity among glacial hydrology, microbial community, and geochemistry and that increases in meltwater discharge from glaciers and ice sheets impact the proglacial systems [ 20 , 198 , 199 , 200 , 201 ]. Therefore, whereas it is clear that climate warming affects and will affect dynamics within glaciers and ice sheets and in their out-stream environments, little information is present on how glacial microbial communities will be impacted.…”
Section: Discussionmentioning
confidence: 99%
“…In the supraglacial environment, organic and inorganic nutrients and carbon are often available in dissolved forms released by the biochemical weathering of deposited particles [ 13 , 126 ]. With the onset of the ablation season, nutrients and carbon deposited during the accumulation season progressively percolate through the snowpack into the weathering crust, cryoconite holes, and glacial ponds (ablation zone) [ 12 , 55 ], and microorganisms are able to resume metabolic activity shortly after thawing [ 20 ] ( Figure 1 ).…”
Section: Hydrology Influences On Glacial Nutrients and Microbial Comm...mentioning
confidence: 99%
See 1 more Smart Citation